PENGARUH INFLASI DAN NILAI TUKAR TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BEI - Uswatun Hasanah; Rizki Simanullang; Ahmad Wahyudi Zein (INTERNATIONAL, Journal of Sharia Business Management, 2026)
This research seeks to examine how inflation and exchange rate fluctuations impact the Composite Stock Price Index (IHSG) through the use of a multiple linear regression technique. The analysis is conducted using secondary data sourced from reputable outlets, evaluated by various statistical methods, which include the t-test, F-test, and the coefficient of determination (R²). The findings indicate that inflation exerts a considerable and positive influence on IHSG, demonstrating that gradual rises in inflation can encourage stock market development. In contrast, the exchange rate exhibits a significant negative impact on IHSG, implying that a weaker rupiah usually leads to diminished stock market results. In summary, the variables relating to inflation and exchange rates account for some of the changes in IHSG, while other aspects that are not included in the model affect the remaining variability. These results underscore the significance of macroeconomic factors in shaping the movements of the capital market in Indonesia.